EPCT-23 PRE-CLINICAL STUDY OF FOCUSED ULTRASOUND-MEDIATED BLOOD-BRAIN BARRIER OPENING AND PANOBINOSTAT FOR DIFFUSE INTRINSIC PONTINE GLIOMA TREATMENT. (1st June 2021) - Wei, Hong-Jian; Pouliopoulos, Antonios; Yoh, Nina; Tazhibi, Masih; McQuillan, Nicholas; Zhang, Xu; Szalontay, Luca; Gartrell, Robyn; Pavisic, Jovana; Zhang, Zhiguo; Feldstein, Neil; Becher, Oren; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is the lethal high-grade brain tumor in children with no effective treatment options to date. Despite excessive clinical trials, the prognosis remains poor, with a median overall survival (mOS) of less than 1 year. Genomic studies of DIPG tissue have identified highly recurrent mutations in genes encoding histone H3 resulting in the substitution of lysine to methionine at position 27 (K27M), which is found in approximately 80% of DIPG. Recent drug screening studies identified the histone deacetylase (HDAC) inhibitors panobinostat as a highly effective drug against DIPG in vitro. However, due to the poor Blood-Brain Barrier (BBB) penetration of systemic administration, to enhance the delivery of panobinostat to improve treatment efficacy is needed. Focused ultrasound (FUS) has been shown to be able to safely and non-invasively open BBB to enhance drug delivery. Hence, in this study, we hypothesize that FUS-mediated BBBO (BBBO) can enhance the delivery of panobinostat for a therapeutic benefit in DIPG. Herein we established the syngeneic DIPG model by intracranially injecting mouse DIPG cells (PDGFB+, H3.3K27M, p53−/−) and used FUS and microbubbles to open BBB and enhance the panobinostat delivery. Magnetic resonance (MR) imaging was utilized to evaluate BBBO and tumor progression. We first demonstrated that FUS-mediated BBB-opening is safe and feasible to mice with DIPG tumors by MR imaging and passive cavitation detection. Moreover, this DIPG cell line is very sensitive to panobinostat in in vitro cytotoxicity assay. The combined treatment of FUS-mediated BBBO and panobinostat showed benefits in both local control and overall survival. The current results demonstrated FUS could increase the treatment efficacy of panobinostat to DIPG animals may be due to the increase of targeted delivery of systemic panobinostat to DIPG tumors in brainstem.